ANALISIS KEMANDIRIAN DAN KEMAMPUAN KEUANGAN DAERAH TERHADAP KEMISKINAN DI KABUPATEN BOGOR - Milda Handayani; Rycha Kuwara Sari; Ari Sulistyowati (Aliansi : Jurnal Manajemen dan Bisnis, 2021)
The regional government holds the mandate of the central government in implementing regional autonomy and has a role in resource management which in turn can improve the welfare of the community. To be able to improve the welfare of the community, one measure can use an analysis of regional financial independence and regional financial capacity by assessing the original regional income compared to total regional income and the balance fund. And see the effect on the percentage of poor. The results obtained, the regional financial independence of Bogor Regency is still in the range of 0% - 25% so that it is categorized as very low, while the regional financial capacity is at 24.07% or it can be said that it is sufficient. Meanwhile, the results of multiple linear regressions for regional financial independence and regional financial capacity have an influence on the percentage of poor people. The expected result is that Bogor Regency can do more to increase its base of tax and retribution revenues so as to minimize budget dependence from the central government and local governments.